Hair Care in the Light of Selected Medieval Medical Treatises - Lisowska, Karolina (Respectus Philologicus, 2023)
In the Middle Ages, hair was an element of great interest to men and women. Subject to daily treatments and activities, they played an important role in everyone‘s life. In medical treatises, compendia and handbooks from the 12th to the 14th century were the subjects of theoretical considerations and practical advice. According to the prevailing humoral theory, their colour, length, shape, and loss or excessive growth were meticulously analysed and explained. Attention was drawn to the issue of hair dyeing and the possibility of changing the colour. Particular attention was paid to baldness and greying, giving practical advice and simple or more complex recipes to prevent these processes. The source base is the works of St. Hildegard of Bingen, pope John XXI, Vincent of Beauvais, Taddeo Alderotti and Bernard de Gordon. In these sawmills, the issue of hair was highlighted, which in the Middle Ages played a significant role in the lives of both women and men.